Demographic factors associated with dietary supplement prescriptions filled by United States Military Service Members 2005–2013. Issue 1 (December 2017) - Knapik, Joseph; Jean, Rosenie; Austin, Krista; Steelman, Ryan; Farina, Emily; Lieberman, Harris
Abstract Background Dietary supplements (DSs) can be purchased over-the-counter but may also be prescribed by medical personnel for specific therapeutic reasons. Few studies have examined this latter source of DSs despite the fact that 79% of physicians and 82% of nurses have recommended DSs to their patients. This investigation examined demographic factors associated with temporal trends in oral DS prescriptions filled by all United States (US) service members (SMs) from 2005 to 2013 (n = 1, 427, 080 ± 22, 139, mean ± standard deviation per year). Methods The Food and Drug Administration National Drug Code database and the formularies of the US Defense Health Agency's Pharmacoeconomic Center were queried to identify DSs available to SMs. The number of these DS prescriptions filled by all SMs from 2005 through 2013 was then obtained from the US Department of Defense Pharmacy Data Transaction System. Data were grouped by American Hospital Formulary System (AHFS) pharmacologic-therapeutic classifications and examined over time. Denominators (number of SMs each year) were obtained from the Defense Health Agency. Results Major findings included 1) generally greater prevalence of prescriptions filled by women and older SMs for most AHFS categories; 2) a temporal decline in total prescriptions filled by Marine Corps personnel accounted for by a decline in the prevalence of zinc preparations filled by younger male Marines; 3) a temporal decline in the prevalence of iron preparations filled by women; 4) a temporal increase in the prevalence of prescriptions for replacement preparations filled by women accounted for largely by more prescriptions for calcium compounds; and 5) a temporal decline in the prevalence of prescriptions filled for cathartics/laxatives in older SMs accounted for largely by a decline in prescriptions for sodium/potassium compounds. Conclusions These temporal trends may be associated with the greater health care utilization of women and older SMs as well as the perceptions of prescribers and/or patients on appropriate roles of these substances in medicine and public health.